1983
DOI: 10.1073/pnas.80.10.2956
|View full text |Cite
|
Sign up to set email alerts
|

Detection of an unusually stable fibrinolytic inhibitor produced by bovine endothelial cells.

Abstract: Fibrin/agar films were prepared and used to detect plasminogen activators produced by cultured bovine aortic endothelial cells (fibrin autography). One preparation of fibrin underwent spontaneous lysis upon incubation at 37TC. This lysis was prevented by antibodies to tissue-type plasminogen activator but not by antibodies to urokinase. Conditioned medium from the confluent endothelial cells was fractionated by polyacrylamide gel electrophoresis in the presence of NaDodSO4. The gels were analyzed on indicator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
170
0
2

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 353 publications
(183 citation statements)
references
References 35 publications
9
170
0
2
Order By: Relevance
“…Furthermore, these inhibitors appear to differ between different cell types. The secretion of Uk inhibitors by murine macrophages, which also synthesize a Uk-type PA (15,16, manuscript in preparation), as well as by hepatoma tissue culture cells (36), endothelial cells (37)(38)(39), and other cell types (40)(41)(42), further underlines the possible generality of these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these inhibitors appear to differ between different cell types. The secretion of Uk inhibitors by murine macrophages, which also synthesize a Uk-type PA (15,16, manuscript in preparation), as well as by hepatoma tissue culture cells (36), endothelial cells (37)(38)(39), and other cell types (40)(41)(42), further underlines the possible generality of these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…1251-labeled fibrinogen was prepared by using the chloramine-T method (11,19 (20). The cells used for these studies had been passaged [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] …”
Section: Methodsmentioning
confidence: 99%
“…The interaction of this urokinase with plasminogen caused the indicator film to lyse. The opaque lysis-resistant zones that develop in the otherwise clear indicator film result from the presence of inhibitors in the NaDodSO4/polyacrylamide gel (14,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the significant enhancement of the mean plasminogen activator inhibitor concentrations, it should be mentioned that it has recently been reported that two pools of plasminogen activator inhibitor-1 exist in blood, which may originate from different cell types. The first one is the free plasma pool, which might be synthesized and secreted by endothelial cells and/or hepatocytes s reported by Loskutoff (28) and Sprengers (39), but this is not unambiguously established. The second pool of plasminogen activator inhibitor has been detennined in the α-granules of the platelets (30) and thus in megakaryocytes.…”
Section: Discussionmentioning
confidence: 99%